Self-Employment around Retirement Age - Stefan Hochguertel (Tinbergen Institute, 2010)
This paper uses panel data from the pan-European SHARE survey to study labor market behavior of older male self-employed vis-a-vis wage employed workers. We find the self-employed to work longer hours, to be more flexible in their hours allocation, and to retire later in all countries. We relate these differences in observed behavior to individual characteristics, economic resources, and to documented cross-national variation in labor market and social security institutions. Differential incentives matter for the retirement behavior of the self-employed. We also provide evidence of the self-employed not wanting to retire as early as possible, and contrast these expectation data with realized retirement transitions. The overall picture that emerges is that older self-employed have a very strong labor market attachment and they use their degrees of freedom to work more and retire later accordingly.
Keywords: J14; J22; J26; L26; 330; self-employment; labor supply; retirement; pensions; Europe; institutions; Arbeitsangebot; Flexible Altersgrenze; Vergleich; Arbeitskräfte; Selbstständige; Europa